Media coverage, corporate social irresponsibility conduct, and financial analysts' performance. (22nd September 2021) - Berkan, Acar; Leonardo, Becchetti; Stefano, Manfredonia
Abstract: We examine how financial analysts respond to public information about corporate social irresponsibility (CSI) conduct. Exploiting a novel dataset on environmental, social, and governance reputational risk rating based on media coverage and analyzing a sample of 667 public corporations over an 11‐year period, we find that analysts' optimistic bias tends to grow in proportion to media coverage of CSI conduct. To deal with the endogeneity issue, we propose as instrumental variable, namely, the Euclidean distance from the Canadian border. The results are robust to the use of different measures of the independent and dependent variables as well as an alternative instrumental variable approach. We also show that over‐optimistic bias is larger when information asymmetries are stronger. Our findings are in line with the rational over‐optimistic behavior hypothesis and have important implications for market efficiency.